Mass Spectrometry-Based Purity Assessment of Hydrogen from Different Production Pathways: Compliance Evaluation with ISO 14687:2019 Standards - Rismen Sinambela (CV. Get Press Indonesia, 2025)
The global transition toward low-carbon energy has positioned hydrogen (H₂) as a key renewable fuel, particularly for applications in fuel cells that require ultra-high purity. Ensuring hydrogen quality is essential to prevent catalyst poisoning and system degradation, as defined in ISO 14687:2019 standards. This study presents a simulation-based analysis of hydrogen purity using a Gas Chromatography–Mass Spectrometry (GC–MS) modeling approach to evaluate three production pathways: green hydrogen (from electrolysis), grey hydrogen (from steam methane reforming), and a fuel cell–grade feedstock.The simulation predicts impurity profiles such as O₂, N₂, CO, CO₂, CH₄, sulfur compounds, and water vapor, comparing each with ISO threshold limits. Results indicate that green hydrogen generally complies with ISO standards, while grey hydrogen exceeds CO₂ and sulfur limits. The fuel cell–grade sample shows near-complete conformity due to simulated purification processes such as pressure swing adsorption.These findings highlight that analytical modeling can effectively predict hydrogen quality and compliance potential across different production routes. The study emphasizes that advancing hydrogen technology requires not only cleaner production methods but also reliable analytical simulations to support quality assurance and sustainability in future hydrogen economies.